Building Energy-Saving Technology - Lin, Yaolin; Yang, Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Buildings consume about 40% of the global energy. Therefore, the building sector plays a key role in achieving the goals of carbon peak and carbon neutrality. Various energy-saving technologies for buildings, such as building envelops, mechanical systems, and energy resources, have been developed to help to achieve zero- or even net-energy buildings while maintaining comfort and a healthy indoor environment. This Special Issue on building energy-saving technology was open to all contributors in the field of building engineering. The original experimental studies, numerical simulations, and reviews in all aspects of building energy utilization, management, and optimization have been considered. For this event, all of these topics were covered in the extensive submissions which were accepted, but interesting papers on other aspects of building energy efficiency were also received. In this reprint, the main research findings of the accepted papers in the Special Issue, including the energy-saving technologies involved in building envelops, mechanical systems, are summarized, and occupant behaviors, and a number of research questions and research directions are identified.